A Research in China Based on the Moral Judgement Test - Yang, Shaogang; Wu, Huihong (ETHICS IN PROGRESS, 2011)
In this research we use “the Moral Judgment Test” as an instrument that is developed by Professor Georg Lind in 1976, but is a Chinese version with some revisions, with 724 students whose ages are from 14 years old to 27 years old as the participants. The results show that: the C-scores are increased with the increase of the students’ age, but there are some fluctuations among different grades. It is obvious that the school education do could improve students’ abilities of moral judgment, but there exist some instability factors. There are no significant differences in their C-scores between male and female students, among different grades within certain schools and universities, and among students with various professions, the key schools and the regular schools as well as the two-year and the four-year college students.